Towards Robust, Authoritative Assessments of Environmental Impacts Embodied in Trade: Current State and Recommendations. (19th February 2018) - Tukker, Arnold; de Koning, Arjan; Owen, Anne; Lutter, Stephan; Bruckner, Martin; Giljum, Stefan; Stadler, Konstantin; Wood, Richard; Hoekstra, Rutger
Summary: Global multiregional input‐output databases (GMRIOs) became the standard tool for tracking environmental impacts through global supply chains. To date, several GMRIOs are available, but the numerical results differ. This paper considers how GMRIOs can be made more robust and authoritative. We show that GMRIOs need detail in environmentally relevant sectors. On the basis of a review of earlier work, we conclude that the highest uncertainty in footprint analyses is caused by the environmental data used in a GMRIO, followed by the size of country measured in gross domestic product (GDP) as fraction of the global total, the structure of the national table, and only at the end the structure of trade. We suggest the following to enhance robustness of results. In the short term, we recommend using the Single country National Accounts Consistent footprint approach, that uses official data for extensions and the national table for the country in question, combined with embodiments in imports calculated using a GMRIO. In a time period of 2 to 3 years, we propose work on harmonized environmental data for water, carbon, materials, and land, and use the aggregated Organization for Economic Cooperation and Development (OECD) Inter‐Country Input‐Output GMRIO as default in combination with detailing procedures developed in, for example, the EXIOBASE and Eora projects. In the long term, solutions should be coordinated by the international organizations such as the United Nations (UN) Statistical Division, OECD, and Eurostat. This could ensure that when input‐output tables and trade data of individual countries are combined, that the global totals are consistent and that bilateral trade asymmetries are resolved.